2014
DOI: 10.1155/2014/898762
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Evacuation of Basal Ganglia Hemorrhage via Keyhole Approach Using an Adjustable Cannula in Comparison with Craniotomy

Abstract: Neuroendoscopic (NE) surgery as a minimal invasive treatment for basal ganglia hemorrhage is a promising approach. The present study aims to evaluate the efficacy and safety of NE approach using an adjustable cannula to treat basal ganglia hemorrhage. In this study, we analysed the clinical and radiographic outcomes between NE group (21 cases) and craniotomy group (30 cases). The results indicated that NE surgery might be an effective and safe approach for basal ganglia haemorrhage, and it is also suggested th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 27 publications
(26 reference statements)
1
54
0
2
Order By: Relevance
“…The pooled analysis (Cho et al, 2006;Feng et al, 2016;Zhang et al, 2014) revealed no statistically difference in death between neuroendoscopic surgery and craniotomy (RR = 0.58, 95% CI 0.26-1.29; p = .18) ( Figure 2).…”
Section: Pooled Analysis Of Death After Neuroendoscopic Surgery Vermentioning
confidence: 99%
See 2 more Smart Citations
“…The pooled analysis (Cho et al, 2006;Feng et al, 2016;Zhang et al, 2014) revealed no statistically difference in death between neuroendoscopic surgery and craniotomy (RR = 0.58, 95% CI 0.26-1.29; p = .18) ( Figure 2).…”
Section: Pooled Analysis Of Death After Neuroendoscopic Surgery Vermentioning
confidence: 99%
“…Based on the criteria described in the methods, 206 irrelevant citations were further excluded based on review of titles and abstracts. Finally, a total of 3 RCTs (Cho et al, 2006;Feng, He, Liu, Yang, & Wang, 2016;Zhang et al, 2014) were included in this meta-analysis (Figure 1). The major characteristics of included studies are depicted in Table 1.…”
Section: Overview Of Literature Search and Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus hematoma evacuation by early craniotomy can eliminate increased intracranial pressure, alleviate midline shift, improve cerebral blood flow surrounding the hematoma, and reduce the mortality rate. 23 Compared with burr-hole drainage and neuroendoscopic surgery, craniotomy is characterized by the more effective reduction of intracranial pressure 24 and low brain rebleeding rate after surgery. Owing to effective decompression, it is particularly suitable for patients with a large hematoma volume, enlarging BGH, or herniation.…”
Section: Discussionmentioning
confidence: 99%
“…Средняя продолжительность хи-рургического вмешательства в основной группе была 138 мин, в контрольной -232 мин. Использование прозрачных портов в эндоскопической хирургии ГИ, по мнению ряда авторов, улучшает исходы хирурги-ческого лечения, снижает летальность, уменьшает продолжительность хирургического вме ша тельства, следствием чего является снижение гнойно-септиче-ских осложнений [6,[8][9][10].…”
unclassified